Merkel Cell Carcinoma: A 28-Year Experience. (August 2020) - Kwan, Kera; Ghazizadeh, Shabnam; Moon, Andy S.; Rünger, Dennis; Sajed, Dipti; Elashoff, David; St John, Maie
Objective: To evaluate the management and recurrence outcomes of head and neck Merkel cell carcinoma (HN-MCC) at a single institution. Study Design: A retrospective review of outcomes in patients with HN-MCC. Setting: A tertiary center from May 1990 to December 2018. Subjects and Methods: Electronic medical records of patients with HN-MCC were reviewed. Results: Sixty cases were included, with 67% (40 of 60) males and a mean age of 73.3 years. Imaging had a moderate sensitivity and specificity for detection of occult disease when compared with histopathologic analysis. Forty-two percent (25 of 60) of patients underwent neck dissection, and 12% (7 of 60) had a sentinel lymph node biopsy (SLNB). There was a high rate of negative SLNB findings. The majority of patients were treated with surgery alone (29 of 60), followed by a cohort (21 of 60) treated with surgery plus adjuvant treatment, and 10 of 60 patients were treated with radiation therapy with or without chemotherapy. Recurrence-free survival was 50%, 45%, and 42% at 1, 2, and 5 years. Conclusions: We report higher recurrence rates and higher negative SLNB result rates than other studies. Our results affirm that imaging may not be a substitute for SLNB and that it had an intermediate ability to identify the occult disease. Traditional predictors, including SLNB and cervical node pathology, may not identify patients at risk for recurrence in HN-MCC. We report similar recurrence rates in patients who had treatment of the cervical nodes by radiation therapy or neck dissection as compared with those who did not receive neck treatment.